2021
DOI: 10.1186/s41239-021-00304-8
|View full text |Cite
|
Sign up to set email alerts
|

The identity changes in online learning and teaching: instructors, learners, and learning management systems

Abstract: Not because of the unexpected global pandemic, but because of the emergence of educational technology and pedagogical innovation, the ways of teaching and learning have been switched to technology integrated modes such as blended and flipped learning which is more than changing to online from face-to-face. Yet, many institutes, which rely on a conventional residential teaching mode or use learning management systems (LMS) as an additive tool, are further struggling to adjust to the new environment. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
(36 reference statements)
1
12
0
1
Order By: Relevance
“…We found that the role of SGT facilitators appeared rather ambiguous and likely waned in a student-centric environment (Table 5 ). There are calls to uphold identity changes or the repositioning of facilitators as “co-participants” to better enhance learning experiences and efficacy during online teaching [ 30 ]. A recent study further found that the most influential factor in determining satisfaction with online courses among medical students was course design instead of facilitator issues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the role of SGT facilitators appeared rather ambiguous and likely waned in a student-centric environment (Table 5 ). There are calls to uphold identity changes or the repositioning of facilitators as “co-participants” to better enhance learning experiences and efficacy during online teaching [ 30 ]. A recent study further found that the most influential factor in determining satisfaction with online courses among medical students was course design instead of facilitator issues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the dialog on transforming from schooling to life, the importance of the notion "identity" has been raised as since identity is a meaningful reception to learners (Kolb and Kolb, 2012;Kwon et al, 2021). Identity encompasses the attitudes and habits that influence learning and the ways in which learners come to understand themselves as learners (Lawson, 2014).…”
Section: What Part Of the Vision Can Be Elaborated?mentioning
confidence: 99%
“…In the dialog on transforming from schooling to life, the importance of the notion “identity” has been raised as since identity is a meaningful reception to learners (Kolb and Kolb, 2012; Kwon et al. , 2021).…”
Section: What Part Of the Vision Can Be Elaborated?mentioning
confidence: 99%
“…У сучасних умовах дедалі більше зростає роль і важливість інноваційних форм та технологій навчання у сфері охорони здоров'я. Традиційні форми навчання поступаються місцем інноваційним засобам, що дає можливість викладачеві максимально раціонально використовувати час заняття та дозволяє легко залучити до навчального процесу учнів, а студенту проявити себе під час самостійної роботи [1,5,7]. Сутність інтерактивного навчання в тому, що навчальний процес організується таким чином, що практично всі студенти виявляються залученими до пізнавальної діяльності [2,3,6].…”
Section: Application Of Information Technologies In the Process Of Teaching Theory And Practice Of Physical Therapyunclassified